Administration, Financial Records - American Geographical Society of New York; Bowman, Isaiah, 1878-1950; Boyd, Louise Arner, 1887-1972 (1934)
Correspondence regarding the publication of Louise A. Boyd's The Fiord Region of East Greenland and Polish Countrysides, as well as Dr. Alexander Forbes Northernmost Labrador.